Bioinformatics in Latin America: ISCB-LA SOIBIO RMB Symposium 2020. Issue 4 (11th June 2021) - Hernández-Rosales, M.
Abstract : This special issue 'Bioinformatics in Latin America: ISCB-LA SOIBIO RMB Symposium 2020' features the papers presented at the ISCB-LA SoIBio BioNetMX 2020 Virtual Symposium held on 28–29 October 2020. This is the first international joint event organized by the Mexican Network for Bioinformatics (RMB), the International Society of Computational Biology (ISCB) and the Iberoamerican Society for Bioinformatics (SOIBIO). The aim of this event is to foster interdisciplinary and multidisciplinary collaborations in research across Exact and Life Sciences.